Teachers’ Commitment and Self-Efficacy as Predictors of Work Engagement and Well-Being - Shu, Kunyao (Frontiers in Psychology, 2022)
In the field of language-education psychology, the psychology of educators was not at the center of attention to some extent, despite the immense attention given to the psychology of students. Recently, positive psychology has become very important as it puts more emphasis on the constructive dimensions of life and it regards individual well-being as a major problem for individuals’ achievement. Since the core of an instructing institution is the educators, their well-being must be prioritized in the academic circumstances to both improve students’ skills and to motivate and inspire participation and involvement in the class. Moreover, teacher engagement is viewed as another significant factor in this realm that refers to people’s outlook toward their job, impacting their emotional attendance and engagement during their presentation. Also, there is an inner force that pushes educators to put more time and strength in maintaining participation in the school that is called educator commitment that is determined on evolving the school builds an emotive connection between educators and schools. It eventually encourages educators to improve their instructing careers and find ways to create a successful educational setting that would enable learners to attain their goals. In addition, teacher self-efficacy, including educators’ convictions in their skill to successfully manage assignments, responsibilities, and difficulties associated with their expert activity, has an important function in affecting key scholastic results in the career setting. By taking the aforementioned constructs, this review of literature provides implications for academics, teachers, and policymakers in search of better considering the functions of commitment and self-efficacy on their work engagement and well-being.